Comparison of the effects of intermittent reperfusion and hypothermia in preventing testicular ischemia-reperfusion injury in the testicular torsion model in rats. Issue 6 (December 2019) - Erdem, Ali Onur; Coşkun, Özge Durmaz; Başer, Ayça Töre; Şirinyıldız, Ferhat; Ek, Rauf; Çulhacı, Nil; Yazici, Mesut; Ozkisacik, Sezen
Summary: Introduction: Reperfusion injury after detorsion in testicular torsion is a clinical problem. This study was planned to investigate the protective effect of intermittent reperfusion in hypothermia-applied testicles. Materials and methods: A total of 40 adult male rats were used, and 5 groups were created: sham (Sh; n = 8), torsion (T; torsion-detorsion) ( n = 8), intermittent reperfusion (IR; n = 8), hypothermia (H; n = 8), and intermittent reperfusion+hypothermia (H+IR; n = 8). The left testicle was removed in all groups except in the Sh group, and it was rotated 3 times counterclockwise, fixed in the scrotum, and left for 4 h. After 4 h, the testicle was detorsioned in the groups T, IR, H, and H+IR. During detorsion, an atraumatic vessel clamp was applied in the proximal part of the vascular structures to prevent any reperfusion of the testicle. The clamp was opened immediately in the group T. In the group IR, the clamp was opened, a reperfusion of 5 s was applied; then, the clamp was closed again, and ischemia was created for 10 s; this procedure was repeated 10 times. In the group H, an ice bag cooling was performed around the testis. The tissue temperature was kept constant at 4 °C using a digital thermometer control. The testicle was cooled using an ice bag in the group H+IR; the same procedure was applied to the IR group. In all groups, reperfusion was performed for 1 h at the end of these procedures. The left testicle was removed from all rats; a portion of each testicle was separated for biochemistry testing, and some was separated for histopathological evaluation. At the end of the procedure, intracardiac blood was taken to examine oxidative stress parameters. At the end of the procedure, all animals were sacrificed after administration of a high dose of anesthesia. Results: The authors observed that the tissue was preserved in the experimental groups and this was statistically significant (p<0.05). It was detected that the tissues were also histopathologically and significantly preserved in the groups IR, H, and H+IR. However, both biochemically and histopathologically, there was no superiority of hypothermia, intermittent reperfusion, or combined application (p>0.05). Discussion: Both hypothermia and intermittent reperfusion alone protect tissue from IR damage. But no studies have been found in which these applications were used together. And as a result of this work, the combination of both methods did not show superiority over the effect they showed when they were used separately. The authors think that these methods can be applied clinically because of their ease of application and no additional costs; however, it should be supported by other studies. Summary table Biochemical evaluation of the left testis with mean and standard deviation scores (experimental and torsion) SOD (%) MPO (mU/mL) GPx (mU/mL) CAT (mU/mL) MDA (nmol/g tissue) T 58.00 ± 11.20 585.76 ± 35.79 587.12 ± 37.38 74.36 ± 12.98 140.66 ± 3.23 Sh 9.25 ± 3.60* 247.02 ± 22.13* 845.40 ± 57.49* 364.65 ± 33.97* 102.13 ± 2.42* H 29.25 ± 8.73* 359.60 ± 38.28* 684.05 ± 29.23* 210.85 ± 26.32* 122.04 ± 2.97* IR 37.00 ± 8.91* 395.69 ± 22.387* 709.20 ± 30.63* 212.88 ± 44.31* 122.19 ± 3.23* H + IR 34.00 ± 5.11* 376.49 ± 23.62* 661.96 ± 18.22* 209.83 ± 38.38* 119.74 ± 3.00* T, torsion; H + IR, intermittent reperfusion + hypothermia; SOD, superoxide dismutase; MPO, myeloperoxidase; GPx, glutathione peroxidase; CAT, catalase; MDA, malondialdehyde; H, hypothermia; IR, intermittent reperfusion; Sh, sham. *P<0.05 compared with the torsion group.